Performing abjection in Wafaa Bilal’s domestic tension - Abdelfattah, Hany Ali Mahmoud (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper is a psychoanalytic literary study of the online performance Domestic Tension (2007) by the Iraqi- American artist Wafaa Bilal. Fundamentally built on the psychoanalytic theories of Sigmund Freud and Jacques Lacan, Julia Kristeva’s theory of abjection is well suited to be the critical tool to analyse the online performance Domestic Tension. This paper questions the performance as a manifestation of abjection that espouses Bilal’s anti-Iraq War stance, by exposing the killing of thousands of Iraqis by the US drones. Furthermore, it investigates how the Brechtian theatrical techniques are used to restrain the cathartic experience of the viewers-cum-shooters, inviting them to ‘disavow’ Bilal’s body, abstain from any cannibalistic desires, and finally to think of the consequences of the US invasion of Iraq.